Estabilidad del catalizador ácido tungstenofosfórico / carbón en esterificación continua etanol - ácido acético. - Ramírez Gonzáles, Jorge Luis (2014)
In this research work, the stability of the tungsten phosphoric acid on activated charcoal catalyst on the continuous esterification of ethanol with acetic acid process, under different conditions, was evaluated. Different activated charcoals from various raw materials were prepared. The dried potato charcoal yielded the best results. The support was obtained by carbonization at 350°C and was activated with HNO3 and then impregnated with HPA using Mg+2 ion as ligand. The reaction was performed in a continuous flow differential reactor at varying conditions of flow, temperature, catalyst composition and reaction time. The conversion was determined by titration with acetic acid. The highest conversion obtained was 30.4% under the following conditions: a flow of 0.04 ml/min, with g of catalyst at 55°C for 2 hours. The activity of the ATP/C.A. increases with the temperature and with support prepared with14M HNO3. The support shows no catalytic activity. The catalyst is deactivated with time.